An alternative visualization of business cycles in chaos - Yap, Su Fei; Ruiz Estrada, Mario Arturo (International Union of Crystallography, 2010)
This paper suggests the application of multi-dimensional graphs in the study of business cycles in the context of chaos theory. The alternative multidimensional graphic method used is known as the Kite-Cartesian space (Ruiz, 2006). The Kite-Cartesian space is an alternative analytical tool for observing changes in the behavior of business cycles from a multi-dimensional perspective. We apply the Kite-Cartesian analysis to assess U.S. business cycles from 1940 to 2005 by trimester. The Kite-Cartesian approach provides optical "snapshots" of the national income make-up at any one point in time, thus revolutionizing existing methods of visualization.